Hubungan Tingkat Kecemasan dengan Kualitas Hidup Pada Pasien Gagal Ginjal Kronik (GGK) yang Menjalani Hemodialisa di Rumah Sakit Bintang Amin - Eka Sartika; Rahma Elliya; Triyoso Triyoso (Malahayati Nursing Journal, 2025)
ABSTRACT Anxiety has a significant impact on the quality of life of patients with Chronic Kidney Disease (CKD) undergoing hemodialysis. Anxiety is caused by uncertainty about disease prognosis, concerns about hemodialysis complications, and significant lifestyle changes due to physical limitations or dependence on medical care. To determine the relationship between anxiety levels and quality of life in chronic kidney disease patients undergoing hemodialysis at bintang amin hospital in 2024 This research used a quantitative method with a cross-sectional design. The sample consisted of 115 respondents who were CKD patients undergoing hemodialysis. The dependent variable was Anxiety Level, the independent variable was Quality of Life. The showed that the independent variable was related to anxiety levels (p-value: 0.000). The Odds Ratio (OR) value was 12.938 (95% CI: 2.734 – 61.232), meaning that individuals experiencing anxiety were 12,938 times more likely to have a poor quality of life. There is a relationship between the level of anxiety and the quality of life in patients with chronic kidney disease (CKD) undergoing hemodialysis at Bintang Amin Hospital in 2024.  Keywords: Anxiety Level, Quality of Life, CKD Patients.  ABSTRAK Kecemasan memiliki dampak signifikan terhadap kualitas hidup pasien dengan Penyakit Ginjal Kronis (GGK) yang menjalani hemodialisis. Kecemasan disebabkan oleh ketidakpastian tentang prognosis penyakit, rasa khawatir akan komplikasi hemodialisis, dan perubahan gaya hidup yang signifikan akibat keterbatasan fisik atau ketergantungan pada perawatan medis. Diketahui hubungan tingkat kecemasan dengan kualitas hidup pada pasien GGK yang menjalani hemodialisa di RS Bintang Amin tahun 2024. Jenis penelitian yang digunakan kuantitatif dengan desain cross sectional. Sampel sebanyak 115 responden, merupakan pasien gagal ginjal yang menjalani hemodialisa. Variabel dependen yaitu Tingkat Kecemasan dan variabel independen berupa Kualitas Hidup. didapatkan variabel independen berhubungan dengan tingkat kecemasan (pv:0,000. Nilai Odd Ratio (OR) 12,938 (95% CI: 2,734 – 61,232) artinya individu yang mengalami kecemasan 12,938 kali lebih beresiko memiliki kualitas hidup yang buruk. Adanya hubungan tingkat kecemasan dengan kualitas hidup pada pasien GGK yang menjalani hemodialisa di Rs Bintang Amin tahun 2024.  Kata Kunci: Tingkat Kecemasan, Kualitas Hidup, Pasien GGK